The Interplay of Law, Local Wisdom, and Carbon Policy: Historical Foundations of Indonesia’s Environmental Regulation - Andhella, Sylviana (Law Review, 2024)
Carbon emissions are one of the leading causes of climate change. Carbon consumption or carbon footprint has been a colossal topic because sustainability can be achieved through carbon emission reduction, as carbon emissions are one of the leading causes of climate change. Indonesia is actively working on environmental conservation, but it continues to face various challenges that require attention. Indonesia's commitment to reducing carbon emissions can be shown through its effort to shift toward low-carbon development. Implementing natural resource management laws in Indonesia has not gained popularity, as they are often viewed as unsupportive of environmental sustainability. The regulation is continuously updated and adjusted to address emerging environmental issues. This research aims to explore how local wisdom contributes to forest conservation using qualitative methodology in the Seruyan District, Central Kalimantan. While regulation on carbon trading in forestry is still ongoing, it can be enriched which states that the community has the same rights and opportunities to actively participate in environmental protection and management. The role of society can be providing advice, opinions, suggestions, objections, and complaints. In this case, the society is the local community that lives near the forest. Incorporating their knowledge of preserving nature and preventing forest fires into the policy can be beneficial.